Hectogram-scale green synthesis of hierarchical 4A zeolite@CuOx(OH)(2−2x) (0 ≤ x < 1) nanosheet assemblies core–shell nanoarchitectures with Superb Congo red adsorption performance. Issue 11 (11th February 2020) - Zhang, Leitao; Huang, Lilan; Zhang, Lei; Lu, Binzhong; Li, Junbo; Xie, Yingfang; Ma, Qiang; Xin, Qingping; Ye, Hui; Zhao, Lizhi; Zhang, Yuzhong; Li, Hong
Abstract : The growth of CuO x Cu(OH)(2−2 x ) (0 ≤ x < 1) nanosheet assemblies on the surface of 4A zeolite transforms poor-performance 4A zeolite adsorbents into high-performance 4A-Cu-300 adsorbents for Congo red study. Abstract : Delicate design of hierarchical nanoarchitectures has become a highly effective strategy to develop novel adsorbents with improved adsorption capacity. Herein, hectogram-scale green fabrication of hierarchical 4A zeolite@CuO x (OH)(2−2 x ) (0 ≤ x < 1) nanosheet assemblies core–shell nanoarchitectures (4A-Cu- T, T was the calcination temperature) with terrific Congo red (CR) dye adsorption performance was achieved through a simple, template-free and surfactant-free hydrothermal approach. A series of characterization techniques, including scanning electron microscopy, transmission electron microscopy, X-ray diffraction and photoelectron spectroscopy demonstrated that all resultant adsorbents featured a core–shell structure with 4A zeolite as core ingredients and CuO x (OH)(2−2 x ) (0 ≤ x < 1) nanosheet assemblies as shell components. The adsorption experimental results pointed out that 4A-Cu-300 with a maximum adsorption capacity of 512.987 mg g −1 showed the best adsorption performance amongst all as-prepared adsorbents, and the adsorption capacity of shell component-CuO x Cu(OH)(2−2 x ) (0 ≤ x < 1) nanosheet assemblies was calculated up to 3685.500 mg g −1 . The shell thickness and phase ratio of CuO and Cu(OH)2 in CuO x (OH)(2−2 x ) (0 ≤ x < 1) nanosheet assemblies played key roles in improving the adsorption capacity. The successive tests suggested that the "carbon deposition" resulted in the decreased adsorption capacity of first-regenerated adsorbents, but little variance in adsorption performance among regenerated samples demonstrated the good stability of such adsorbents. This work unlocks a method for the rational design of high-performance adsorbents via delicate decoration of poor-performance materials with nanosheet assemblies, which will endow the non-active materials with enhanced adsorption properties.